How I, Nicky Flynn, finally get a life (and a dog) : a novel - Corriveau, Art (Amulet Books, 2010)
Moving to inner-city Boston after his parents' divorce, eleven-year-old Nicky struggles to cope with the changes in his life, including acquiring a former guide dog that leads to a mystery for Nicky to solve.